Development and validation of an innovative headspace collection technique: volatile organic compound patterns emitted by different developmental stages of Halyomorpha halys - Karimi, Ali; Gross, Jürgen (Frontiers in Horticulture, 2024)
Over the past two decades, several headspace collection techniques have been used to detect and identify volatile organic compounds (VOCs) emitted by plants, pests, air, and soil. Volatiles emitted by pests and infected plants are usually found at low concentrations. The important challenge is to be able to capture an exact collection of relative quantities of the relevant VOCs. Here we present an innovative headspace collecting device (HSCD) for sampling VOCs, which ensures an exact regulation of mass flow velocity and collected total gas volume allowing besides qualitative analysis of collected VOCs, an exact comparison of their relative quantities in plant or insect headspace samples. The HSCD possess six parallel odor collection systems each consisting of a digital mass flow detector and controller connected to a vacuum pump, which are mounted in a trolley suitcase, connected by tubes, and wired electrically. The programming of the channels, can be done by a digital control unit. Using the HSCD, VOCs emitted by the brown marmorated stink bug (BMSB), Halyomorpha halys, from its different developmental stages including egg, nymphal stages, nymphal exuvia, and adults were collected on thermal desorption tubes and analyzed using an automated thermal desorber connected to a gas chromatography-mass spectrometry system. Forty-five VOCs were identified in total, which mainly consisted of tridecane (4.36-69.33 %), E-2-decenal (4.24-26.48 %), 2-undecenal (0.63-50.03 %), and E-4-oxo-2-hexenal (1.22-20.58 %). The random forest analysis revealed three different chemical patterns among BMSB life stages samples. In conclusion, these results indicate that the new developed HSCD, a mobile, easy to use, and reliable instrument, has a high potential to sample relevant VOCs of a specific life stage of an insect both qualitatively and quantitatively. It was demonstrated that this information can be used for identifying specific chemical signatures, which fit to specific life stages of the BMSB, and may be used as biomarker for on-site detection of this pest e.g. in shipping containers or agricultural areas.